2017
DOI: 10.1080/13102818.2017.1342562
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cultivation conditions in banana wastes for production of extracellular β-glucosidase byTrichoderma harzianumRifai efficient forin vitroinhibition ofMacrophomina phaseolina

Abstract: The present study was carried out to optimize the physical and nutritional parameters for cultivation of Trichoderma harzianum Rifai for production of extracellular b-glucosidase, an alternative to chemcial fungicides to control Macrophomina phaseolina, which causes charcoal rot disease in crops. Response surface methodology by the Box-Behnken design (BBD) based on four factors (temperature, carbon sources, inoculum size and pH) was used for optimization of the cultivation conditions to produce b-glucosidase u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It is well-known that inhibition of βglucosidase activity of fungus prevent fungal pathogenicity in host plants. 13,[21][22][23] Several experimental studies revealed that leaf volatile oil of T. errecta has potent antifungal activities, 5,24 but the prediction of lead compound(s) is an important task to know the design of fungistatic compound. Although, the isolation of lead compound(s) followed by in vitro and in vivo study is suggesting in future research.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that inhibition of βglucosidase activity of fungus prevent fungal pathogenicity in host plants. 13,[21][22][23] Several experimental studies revealed that leaf volatile oil of T. errecta has potent antifungal activities, 5,24 but the prediction of lead compound(s) is an important task to know the design of fungistatic compound. Although, the isolation of lead compound(s) followed by in vitro and in vivo study is suggesting in future research.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that among the well-described antagonistic mechanisms for the fungal isolate, T. harzianum (nutrient competition, antibiotic production and mycoparasitism) (KUBICEK et al, 2001;VITERBO et al, 2002;GAJERA et al, 2010;KHALILI et al, 2016), its mycoparasitic behaviour is particularly interesting. T. harzianum has evolved the capability to secrete a type of β-glucosidase that digests the ordered layers of amorphic β-1, 3-glucan (GAJERA et al, 2010;KHALILI et al, 2017) in M. phaseolina. The hydrolytic activity of this βglucosidase targets the sugar-based polymer that forms the filling material in the chitin-based cell wall of the pathogenic fungus (GAJERA et al, 2010;KHALILI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…T. harzianum has evolved the capability to secrete a type of β-glucosidase that digests the ordered layers of amorphic β-1, 3-glucan (GAJERA et al, 2010;KHALILI et al, 2017) in M. phaseolina. The hydrolytic activity of this βglucosidase targets the sugar-based polymer that forms the filling material in the chitin-based cell wall of the pathogenic fungus (GAJERA et al, 2010;KHALILI et al, 2017). Driven by this knowledge, we believe that the enzyme may prove useful as an alternative bioactive component in a fungicide to inhibit proliferation of M. phaseolina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation